Islamic financial literacy scale: An amendment in the sphere of contemporary financial literacy - Yusuf Dinc; Mehmet Çetin; Mehmet Bulut; Rashed Jahangir (ISRA International Journal of Islamic Finance, 2021)
Purpose - This study aims to develop a valid and reliable Islamic financial literacy (IFL) scale that can capture all the segments of the Islamic financial sectors and which could be considered applicable for all jurisdictions across the globe. Design/methodology/approach - To build the measure, this study followed a scale development process by collecting 698 a priori items from 81 respondents. Later, it generated an item pool through the analysis of the items with experts and gave the last form (40 items) to 287 respondents in Turkey with another IFL scale that is frequently used in the literature and a scale assessing religiosity. With explanatory factor analysis, the scale demonstrates a four-factor construct with 20 items. This construct provides good fit indexes and reliability scores. Findings - Results of the correlation analysis and comparison of the fit indexes of alternative structures provided supportive evidence for discriminant and convergent validity of the scale and its sub-dimensions. As a result, an applicable scale is developed for countries where Islamic financial institutions are operating and where they are not. Originality/value - One of the strengths of this study is that it represents a comprehensive scale development for the entire Islamic financial system, including banking takāful (Islamic insurance) and fund management. In addition, the attempt to design an IFL scale applicable to any economy or individual is a pioneering attempt in the literature.
Keywords: 330; Islamic banking; Islamic finance; Islamic insurance; Literacy; Takāful